2017
DOI: 10.1063/1.4979642
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical properties of electrostrictive CeO2:Gd membranes: Effects of frequency and temperature

Abstract: Doped ceria is known for decades as an excellent ionic conductor used ubiquitously in fuel cells and other devices. Recent discovery of a giant electrostriction effect has brought world-wide interest to this class of materials for actuation applications in micromechanical systems. From this aspect, the electromechanical response has to be studied as a function of external parameters, such as frequency, temperature, and electrode material. In this work, we fabricated circular membranes based on Gd-doped ceria (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…We have demonstrated that the electrode material [10] becomes even more important in the high operating frequency range (100 Hz-10 kHz). The principally different behavior of the membranes with Al and Ti electrodes at low frequencies is attributed to the formation of Schottky-barriers at the Al electrode/material interface, while at frequency about few MHz both membranes become thermally excited.…”
Section: Introductionmentioning
confidence: 95%
“…We have demonstrated that the electrode material [10] becomes even more important in the high operating frequency range (100 Hz-10 kHz). The principally different behavior of the membranes with Al and Ti electrodes at low frequencies is attributed to the formation of Schottky-barriers at the Al electrode/material interface, while at frequency about few MHz both membranes become thermally excited.…”
Section: Introductionmentioning
confidence: 95%
“…Despite intriguing, some questions about the role of oxygen vacancies and microstructure on electrostriction still remains unexplored [12]. Besides, Lubomirsky and coworkers suggested a power law dependence of I-V relationship in grain boundary blocking behavior based on space charge mechanisms [18] [19] and demonstrated that an increase of grain boundary resistance leads to a decrease in the portion of applied voltage drop in the bulk, decreasing electromechanical properties [20].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have demonstrated the feasibility of mechanical actuation with CGO‐based devices and have shown that the choice of contact metal is critical for functionality . Of the electrodes tested, titanium contacts were found to display the lowest resistance . However, the electromechanical response of micro‐electromechanical systems (MEMS) based on CGO films was found to be complex .…”
Section: Introductionmentioning
confidence: 99%